Bibliometric Analysis and Visualization of Academic Procrastination - Tao, Xue; Hanif, Hafiz; Ahmed, Hamsa Hameed; Ebrahim, Nader Ale (Frontiers in Psychology, 2021)
Numerous students suffered from academic procrastination because it’s a common problem and phenomenon in academic settings. Many previous researchers have analyzed its relations with other factors, such as self-regulation, academic performance, etc. In this paper, Bibliometrix and VOSviewer were used to conduct quantitative analysis and give a fully outline of academic procrastination and to catch the current hotspots and trends. The data was collected from the Web of Science core collection database which contains 1240 articles from the year 1938 to 2021. In specific, the trends of publication and the classification of articles may shed light on current trends and areas of academic procrastination research. This bibliometric paper mainly contains the analysis of authors, the most influential journals, institutions, and countries. The theoretical knowledge and research hotspots about academic procrastination mainly include “procrastination”, “academic procrastination”, “self-regulation”, “academic performance”, and “motivation”. Therefore, this paper is helpful for scholars and practitioners to comprehensively know the trend of academic procrastination research.